2019
DOI: 10.1159/000495989
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hand-Foot Skin Reaction with Regorafenib Efficacy in the Treatment of Metastatic Colorectal Cancer

Abstract: Purpose: Hand-foot skin reaction (HFSR) can deteriorate quality of life in patients receiving regorafenib. Cutaneous toxicity is a main adverse effect of multikinase inhibitors and has also been associated with clinical outcome. This study assessed the association between the antitumor efficacy of regorafenib and HFSR in patients with metastatic colorectal cancer (mCRC). Methods: Patients who received regorafenib at 160 mg/day during the first 3 weeks of each 4-week cycle were divided into subgroups based on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
1
14
1
1
Order By: Relevance
“…The hand-foot syndrome was proposed to be a predictive biomarker for assessing the efficacy of anti-angiogenic drugs. 36,37 In our study, patients who had hand-foot syndrome had a median PFS of 8.0 (95% CI 1.7-14.3) months, compared to 3.0 (95% CI 1.6-4.4) months in those who did not, but the significant difference was not achieved (p=0.163).…”
Section: Discussionmentioning
confidence: 54%
“…The hand-foot syndrome was proposed to be a predictive biomarker for assessing the efficacy of anti-angiogenic drugs. 36,37 In our study, patients who had hand-foot syndrome had a median PFS of 8.0 (95% CI 1.7-14.3) months, compared to 3.0 (95% CI 1.6-4.4) months in those who did not, but the significant difference was not achieved (p=0.163).…”
Section: Discussionmentioning
confidence: 54%
“…As favorable clinical factors associated with OS in regorafenib therapy, we revealed that 1M-RDI ≥ 50% (HR 0.16, 95% CI 0.05–0.50, p = 0.001) and HFSR during regorafenib therapy (HR 0.06, 95% CI 0.01–0.28, p = 0.0004) were independently associated with OS. Previous studies [23,24,25] reported that patients with metastatic colorectal cancer who were treated with regorafenib—and who experienced HFSR—showed better OS than patients without HFSR. The correlation of HRSR and survival has also been reported in the patients who enrolled the RESORCE trial [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognosis of TKIs is favorable despite the appearance of AEs. In particular, the appearance of hand-foot syndrome (HFS) is reportedly correlated with prognosis for several TKIs (11)(12)(13). This retrospective study aimed to verify the AEs of lenvatinib in the real-world setting and clarify whether life-threatening AEs and HFS are markers of good prognosis as previously reported.…”
Section: Introductionmentioning
confidence: 91%
“…The frequency of HFS is high in Japan, as has been reported for several TKIs (13). Although the precise mechanisms by which multikinase inhibitors cause HFS remain unknown, the antiangiogenic activity of these drugs may inhibit vascular repair mechanisms in high-pressure areas, such as the palms and soles, which are repeatedly exposed to subclinical trauma (23).…”
Section: Characteristics Of Aes Aementioning
confidence: 96%